STRATEGI KOMUNIKASI PEMASARAN YANG DILAKUKAN OLEH PEDAGANG SAYURAN DI PASAR MAYESTIK PADA MASA PANDEMI VIRUS COVID-19 - Rania, (2022)
The Covid-19 virus pandemic has had many negative impacts on the wider community, especially in terms of the economy. The economic impact is felt by vegetable traders in the Mayestik market, namely the reduced income they get, so they have to make marketing communication strategies that are in accordance with the conditions during the Covid-19 period. This study was conducted with the aim of knowing the marketing communication strategies carried out by vegetable traders at the Mayestik market during the Covid-19 virus pandemic. The method used in this research is a qualitative research method with a case study approach. The results obtained in this study are that vegetable traders in the Mayestik market carry out marketing communication strategies by conveying directly to their customers that they can be ordered online, and also by utilizing social media such as whatsapp, Instagram, or e-commerce such as grab. The local market also helps by using social media Instagram. Vegetable traders and also the local market also always maintain cleanliness in the local market environment and implement health protocols in the local market.